Menyame Beraya: The Attitudes to Prevent Intolerance in Silent Day - I Ketut Suda; Ni Made Indiani (Politeknik Negeri Bali, 2018)
The existence of local wisdom possessed by Balinese people can be said to be threatened by social changes and cultural dynamics in the modern era as it is today which is characterized by the values of modernism which are all effective, fast, and tend to be individualistic. These caused Balinese people change such as almost forgetting the noble values that they once had, such as sagalak-sagilik-saguluk, salunglung sabayantaka, paras paros sarpenaya, menyama beraya, having a harmonious attitude. Through this paper, it will be discussed whether the concept of ‘menyama beraya‘ is still useful to prevent intolerance during silent day (or in a holy day = Nyepi). The conclusion that can be drawn is that through the celebration of Nyepi, tolerance can be built in social life, through the implementation of ‘catur brata penyepian’ . However, in reality this cannot be done optimally, considering the transmission of the values of social wisdom and the values of traditional wisdom that should be carried out by the family towards children has not run optimally. The concept of menyama beraya as one of the values of Balinese social wisdom, cannot yet be applied optimally in the present context, because modernism causes things that are traditional to be transformed. It is suggested that parents should socialize the values ​​of social wisdom, the values ​​of traditional wisdom, and the values ​​of local wisdom to their children. By doing this way children will not be uprooted from their cultural roots, even though they cannot avoid the influence of global culture.